Extracting the maximum energy from solar panels - Mohamed Nfaoui; Khalil El-Hami (Energy Reports, 2018)
The performance of solar systems to convert solar radiation depends on its inclination angle to the horizontal plane, independently from meteorological conditions. Sunlight should fall with steep angle to extract maximum power from solar panels. Therefore, optimum fixed tilt angles of solar panels should be changed monthly and seasonally. In our study, MATLAB program is used to estimate the total solar radiation on a tilted panel surface with any inclination. The implementation developed to allow us to extract the correct angle at which the maximum energy could be absorbed by the solar cells. We could determine the optimum tile angle for monthly, seasonal, and yearly solar radiation relative to the site of Khouribga city (latitude 32°52′ North and longitude -6°54′ West), and we used the same method to draw the table of solar gains depending on the optimum tilt angle of the solar panels to the main Moroccan cities.
Keywords: 330; Energy; Solar radiation; Optimum tilt angle; Inclination